Assessment of helmet usage among secondary school students in urban settings: A descriptive analytical study from Karachi, Pakistan - Mazhar Iqbal; Kashif Shafique; Mariam Ashraf (PLoS ONE, 2026)
Introduction In Pakistan, the burden of road crashes continues to escalate due to inadequate traffic law enforcement and low helmet usage. This study assesses the knowledge, attitudes, and practices of adolescent motorbike riders regarding safe riding practices and helmet use. Methods A descriptive-analytical study was conducted in public-sector secondary schools in Karachi among male students aged 15–19 years, using a structured questionnaire based on the Health Belief Model (HBM) and the Theory of Planned Behaviour (TPB). Data collection took place from October -December 2022. Results A total of 502 students participated in the survey. The average age of the participants was 16.80 ± 1.20 years. Socio-economic data showed that most individuals belonged to the lower-middle class (63%, n = 319), with 25% (n = 125) owning personal motorcycles and 32% (n = 163) riding as passengers. The majority rode daily, with 27% (n = 137) reporting accidents without wearing helmets. Results consistent with HBM and TPB suggest a good understanding of helmet benefits but acknowledge obstacles such as helmet costs. Attitudes towards safety varied, with intentions to wear helmets immediately ranging from 24% to 29%. Lower HBM scores were more frequently observed among those from the lower-middle class (63%, n = 319) and lower socio-economic class (30%, n = 151), showing a significant association (p value = 0.002), indicating a possible disparity in knowledge and attitudes towards road safety across different socio-economic groups. Those who rode as passengers or were self-riders generally had lower HBM scores compared to others (p < 0.001). Conclusions The findings indicated that while most students recognised that helmet use is important for safety, they demonstrated limited knowledge of proper helmet usage, traffic regulations, and other road safety measures, reflecting a gap between basic awareness and comprehensive safety knowledge.